Pengaruh Pelatihan Dan Disiplin Terhadap Kinerja Karyawan Pada PT. Kojo Badak Di Muara Badak - Arisman Arisman; Joko Sabtohadi; Bambang Sukma Alam (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
Abstract:The purpose of the study are to to see if in full and simultaneous training and discipline significant impact on employee performance he would do to pt .Kojo in muara rhinoceros .The form of survey research is research , the approach that was used explanation reseach and , the results of the analysis is the variable training and discipline and good in full simultaneous have had a positive impact and significant on variables the employee performance he would do to PT. Kojo rhinoceros in kecamatan muara rhinoceros . Keywords: training , discipline, and the employee performance